Rest to Promote Learning: A Brain Default Mode Network Perspective - Wei Luo; Biao Liu; Ying Tang; Jingwen Huang; Ji Wu (Behavioral Sciences, 2024)
The brain often switches freely between focused attention and divergent thinking, and the Default Mode Network (DMN) is activated during brain rest. Since its discovery, the DMN, together with its function and characteristics, indicates that learning does not stop when the brain “rests”. Therefore, DMN plays an important role in learning. Neural activities such as beta wave rhythm regulation, “subconscious” divergence thinking mode initiation, hippocampal function, and neural replay occur during default mode, all of which explains that “rest” promotes learning. This paper summarized the function and neural mechanism of DMN in learning and proposed that the DMN plays an essential role in learning, which is that it enables rest to promote learning.